(untitled) (Sciences & Technology. A, exactes sciences, 2002)
In this paper, we present an off line method of Arabic Handwritten Characters Recognition. The study is based on the analysis of several performances of feature vectors. It is hoped that the results of the evaluation contribute to the conception of operational systems. The futures are the projection moments, Barr-features, and Fourier descriptors. The classification is achieved by a standard multi-layer perception.